Effect of Profitability, Sales Growth, Corporate Governance and Leverage on Tax Avoidance Moderated by Executive Character in Mining Sector Companies Listed on the Indonesia Stock Exchange 2016-2019 - Islami Safaati; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2022)
The study in this study aims to determine the effect of Profitability, Sales growth, Corporate Governance and Leverage on Tax Avoidance moderated by Executive Character in Mining Sector Companies Listed on the Indonesia Stock Exchange 2016-2019. This type of research is quantitative. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2016-2019. Determination of the research sample based on the purposive sampling method with a total sample of 76. The data used is secondary data originating from the company's financial statements obtained from the IDX. Secondary data processing using SPSS analysis technique with multiple regression analysis method. The results showed that the executive character was able to moderate the relationship between ROA and tax avoidance. on the other hand, the executive character variable is not able to moderate the relationship between Sales Growth, independent commissioners and leverage on tax avoidance.